2011
DOI: 10.4061/2011/132958
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsecosteroidal Vitamin D Receptor Modulator Ameliorates Experimental Autoimmune Encephalomyelitis without Causing Hypercalcemia

Abstract: Vitamin D receptor (VDR) agonists are currently the agents of choice for the treatment of psoriasis, a skin inflammatory indication that is believed to involve an autoimmune component. 1,25-dihydroxyvitamin D3 [1,25-(OH)2D3], the biologically active metabolite of vitamin D, has shown efficacy in animal autoimmune disease models of multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease, and type I diabetes. However, the side effect of 1,25-(OH)2D3 and its synthetic secosteroidal analogs is hyperca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…[3] Recent investigations suggest that this effect requires a functional VDR on T-lymphocytes , [34] as previously observed, [35] and involves modulation of Th17 cell differentiation and IL-17a expression. [36] STAT6 also appears necessary for amelioration of EAE following 1,25(OH)2D3 treatment in ex vivo studies. [37] Calcitriol, however, can cause hypercalcemia, and its effect may in part be mediated by increased calcium levels.…”
Section: Animal Models Of Msmentioning
confidence: 99%
“…[3] Recent investigations suggest that this effect requires a functional VDR on T-lymphocytes , [34] as previously observed, [35] and involves modulation of Th17 cell differentiation and IL-17a expression. [36] STAT6 also appears necessary for amelioration of EAE following 1,25(OH)2D3 treatment in ex vivo studies. [37] Calcitriol, however, can cause hypercalcemia, and its effect may in part be mediated by increased calcium levels.…”
Section: Animal Models Of Msmentioning
confidence: 99%
“…More importantly, serum calcium levels were within the normal range after compound A treatment versus 1,25-(OH) 2 D 3 . Ex vivo stimulation of total splenocytes from diseased mice revealed that compound A inhibited both T H 1 and T H 17 cell differentiation (Na et al, 2011).…”
Section: Vitamin D Receptor Modulatorsmentioning
confidence: 99%
“…[10] Since the supraphysiological doses of 1α,25(OH)2D3 required to demonstrate the stout anti- inflammatory effects also stimulate hypercalcemia, vitamin D analogs were synthesized in order to potentiate the anti- inflammatory properties of VDR agonists without inducing the hypercalcemic side effects. [11]…”
Section: α 25(oh)2d3 and Vdrmentioning
confidence: 99%